Factors related to the nutritional status of infants aged 0-24 months in Huta Koje Village, District of Southeast Padangsidimpuan City, Padangsidimpuan City - fitri Tanjung, Adelina (Universitas Efarina, 2020)
This research was conducted in 2022 in Huta Koje Village, Padangsidimpuan Tenggara sub-district. This study aims to determine the relationship between the duration of breastfeeding and the nutritional status of infants, to determine the relationship between complementary feeding and the nutritional status of infants and to determine the relationship between weaning and the nutritional status of infants in the village of Huta Koje. In this study, researchers used a cross-sectional method which aimed to determine the relationship between the duration of breastfeeding, early complementary feeding, early weaning of infants with the nutritional status of infants in Huta Koje Village, Padang Sidimpuan Southeast District. Anthropometry by measuring baby's weight based on body weight per baby's age. Body weight is one of the parameters that provide an overview of body mass. Body mass is very sensitive to sudden changes, such as a decrease in appetite, due to infection and a decrease in the amount of food consumed. Body weight is an anthropological parameter. From the results of this study, it was found out the relationship between the length of time the baby was breastfed, the provision of MP-ASI with nutritional status and the relationship between weaning. It was found that the duration of breastfeeding had a relationship with nutritional status, the provision of MP-ASI also had a relationship with the nutritional status of infants while in this study weaning did not have a significant relationship with the nutritional status of infants. due to infection and a decrease in the amount of food consumed. Body weight is an anthropological parameter. From the results of this study, it was found out the relationship between the length of time the baby was breastfed, the provision of MP-ASI with nutritional status and the relationship between weaning. It was found that the duration of breastfeeding had a relationship with nutritional status, the provision of MP-ASI also had a relationship with the nutritional status of infants while in this study weaning did not have a significant relationship with the nutritional status of infants. due to infection and a decrease in the amount of food consumed. Body weight is an anthropological parameter. From the results of this study, it was found out the relationship between the length of time the baby was breastfed, the provision of MP-ASI with nutritional status and the relationship between weaning. It was found that the duration of breastfeeding had a relationship with nutritional status, the provision of MP-ASI also had a relationship with the nutritional status of infants while in this study weaning did not have a significant relationship with the nutritional status of infants. the provision of MP-ASI with nutritional status and the relationship between weaning. It was found that the duration of breastfeeding had a relationship with nutritional status, the provision of MP-ASI also had a relationship with the nutritional status of infants while in this study weaning did not have a significant relationship with the nutritional status of infants. the provision of MP-ASI with nutritional status and the relationship between weaning. It was found that the duration of breastfeeding had a relationship with nutritional status, the provision of MP-ASI also had a relationship with the nutritional status of infants while in this study weaning did not have a significant relationship with the nutritional status of infants.